2010
DOI: 10.1021/jp905569r
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Carbon Monoxide on Pt (335) and (112) Surfaces

Abstract: Adsorption of carbon monoxide on Pt (335) and (112) stepped surfaces has been investigated by the extended LEPS (London-Eryring-Polanyi-Sato) method which is constructed by the 5-parameter Morse Potential. The calculated results show there have common characteristics of CO adsorption on the two surfaces. On both Pt (335) and (112) stepped surfaces, CO molecules adsorb on the step top site initially. With the coverage increasing, CO molecules diffuse from the step top sites to the stable terrace bridge sites an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…4). Also drawn in (c) is a post-dosed CO molecule adsorbing atop partially or even fully H-saturated step sites [3,62,[70][71][72], strongly pushing nearby H atoms at step-edge sites (β 3 -H atoms), and possibly even the nearest H atom adsorbed at FCC sites on the upper terrace, into subsurface tetrahedral and/or octahedral interstitial sites along the speculative dotted purple path(s), in accord with our data on the lower panel of Fig. 5.…”
Section: Further On the Low-temperature β 1 -H Defect Statementioning
confidence: 99%
“…4). Also drawn in (c) is a post-dosed CO molecule adsorbing atop partially or even fully H-saturated step sites [3,62,[70][71][72], strongly pushing nearby H atoms at step-edge sites (β 3 -H atoms), and possibly even the nearest H atom adsorbed at FCC sites on the upper terrace, into subsurface tetrahedral and/or octahedral interstitial sites along the speculative dotted purple path(s), in accord with our data on the lower panel of Fig. 5.…”
Section: Further On the Low-temperature β 1 -H Defect Statementioning
confidence: 99%
“…Pectinase facilitates the breakdown of pectin in cell walls, leading to a more efficient release of β-carotene from chloroplasts. Recent studies have shown that, under specific ultrasonic intensity conditions, low-frequency ultrasonication can enhance the activity of enzyme preparations (Le and Nguyen, 2013;Wu et al, 2014;Wang et al, 2017;Osete-Alcaraz et al, 2019;Larsen et al, 2021;Gamage and Choo, 2023). Therefore, ultrasoundassisted enzymatic extraction (UAEE), which employs the synergistic interaction of enzymatic hydrolysis and ultrasound, could fulfil the requirement for extracting carotenoids from lemon peels.…”
Section: Introductionmentioning
confidence: 99%
“…Studies most relevant to this work are summarized below. Because of their unique coordination environment, Pt atoms at step sites and on flat terraces can be electronically different, which results in higher binding strength of CO molecules adsorbed at on-top sites on the upper part of step sites, compared with that of CO on terrace sites. ,,,, There are significant differences in the IR spectra of the CO adlayer on stepped Pt surfaces with different terrace widths, revealing that the presence of periodic steps greatly influences the CO adlayer structure . However, previous efforts to interpret the surface structure of adsorbed CO based on the IR spectra have led to contradictory conclusions.…”
Section: Introductionmentioning
confidence: 99%